2022
DOI: 10.3389/fsurg.2022.980477
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a nomogram to predict complications in patients undergoing simultaneous bilateral total knee arthroplasty: A retrospective study from two centers

Abstract: PurposeComplications were significantly increased 30 days after Simultaneous bilateral total knee arthroplasty (SBTKA). In this study, an individualized nomogram was established and validated to predict the complications within 30 days after SBTKA.MethodsThe general data of 861 patients (training set) who received SBTKA in The Affiliated Hospital of Qingdao University between January 1, 2012 and March 31, 2017 were retrospectively analyzed. All patients were divided into complication group (n = 96) and non-com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
1
0
0
Order By: Relevance
“…[28][29][30] Nomogram has been widely studied in predicting clinical outcomes after orthopedic surgery. [31][32][33] The nomogram prediction model constructed based on the identified risk factors in the current study also showed a good prediction performance, which is consistent with the findings by Liu et al 10 The score of our nomogram model may be used to calculate the risk of postoperative chronic pain. The specified indicators are easy to obtain in clinical practice, which allows to perform early intervention.…”
Section: Discussionsupporting
confidence: 90%
“…[28][29][30] Nomogram has been widely studied in predicting clinical outcomes after orthopedic surgery. [31][32][33] The nomogram prediction model constructed based on the identified risk factors in the current study also showed a good prediction performance, which is consistent with the findings by Liu et al 10 The score of our nomogram model may be used to calculate the risk of postoperative chronic pain. The specified indicators are easy to obtain in clinical practice, which allows to perform early intervention.…”
Section: Discussionsupporting
confidence: 90%